Developing an international Pseudomonas aeruginosa reference panel. Issue 6 (11th November 2013) - De Soyza, Anthony; Hall, Amanda J.; Mahenthiralingam, Eshwar; Drevinek, Pavel; Kaca, Wieslaw; Drulis‐Kawa, Zuzanna; Stoitsova, Stoyanka R.; Toth, Veronika; Coenye, Tom; Zlosnik, James E. A.; Burns, Jane L.; Sá‐Correia, Isabel; et al.
Abstract Pseudomonas aeruginosa is a major opportunistic pathogen in cystic fibrosis (CF) patients and causes a wide range of infections among other susceptible populations. Its inherent resistance to many antimicrobials also makes it difficult to treat infections with this pathogen. Recent evidence has highlighted the diversity of this species, yet despite this, the majority of studies on virulence and pathogenesis focus on a small number of strains. There is a pressing need for a P. aeruginosa reference panel to harmonize and coordinate the collective efforts of the P. aeruginosa research community. We have collated a panel of 43 P. aeruginosa strains that reflects the organism's diversity. In addition to the commonly studied clones, this panel includes transmissible strains, sequential CF isolates, strains with specific virulence characteristics, and strains that represent serotype, genotype or geographic diversity. This focussed panel of P. aeruginosa isolates will help accelerate and consolidate the discovery of virulence determinants, improve our understanding of the pathogenesis of infections caused by this pathogen, and provide the community with a valuable resource for the testing of novel therapeutic agents.